Response of Different Levels of Nitrogen and Spacing on Growth and Yield of Cauliflower Grown under Central Region of Punjab - Kaur, Pawandeep; Singh, Sandeep Kumar; Kaur, Rajneet; Sidhu, Mandeep Kaur (International Journal of Bio-resource and Stress Management, 2020)
A field experiment was conducted to study theresponse of different levels of nitrogen and spacing on growth and yield of cauliflower at Experimental Farm, Department of Agriculture, Mata Gujri College, Fatehgarh Sahib, Punjab, India from October 2018 to February 2019. The present study was conducted to determine the optimum level of nitrogen and spacing for better growth and yield of cauliflower. The experiment consisted of two factors: Factor A: Nitrogen (4 levels), N0: 0; N1: 50; N2: 75 and N3: 100 % ha-1 and Factor B: Spacing (3 levels), S1: 45×30 cm2; S2: 45×45 cm2 and S3: 60×45 cm2. The experiment was laid out in Factorial Randomized Block Design (FRBD) with three replications. Maximum plant height (54.27 cm), plant spread (69.53 cm), number of leaves plant-1 (17.00), leaf length (46.60 cm), leaf width (25.03 cm), fresh weight of curd (833.33 g), dry matter of curd (0.89 g) was found from N100S60×45. However, maximum curd yield plot-1 (30.03 kg) and ha-1 (326.90 q) was obtained from N100S45×30. while, maximum net return (`299443.45) and B: C ratio (3.22) was obtained with 100 % N ha-1 + 45×30 cm2. Results demonstrated that treatment combination N100S60×45 found to be best in most growth and yield characteristics in cauliflower variety Golden-75 but the maximum yield plot-1 and ha-1 was recorded in N100S45×30 and T0 (Control) gave poor results in all traits.